(untitled) (Comprehensive Journal of Science, 2025)
Power shafts are the most crucial components of a machine, and they are frequently subject to fatigue due to variable external loads. The goal of this research is to design solid and hollow shafts with constant load and torque in order to anticipate the percentage reduction in shaft mass and change in diameter. The modified Goodman approach was used to calculate the shaft’s diameter, which was then compared to the maximum shear stress method. The results show that hollow shafts have a 28% lower mass than solid shafts with the same material and strength, while hollow shafts have a 5% higher outer diameter. When using maximu